PENGUKURAN KINERJA KEUANGAN BERDASARKAN LAPORAN ARUS KAS PADA KOPERASI PEGAWAI REPUBLIK INDONESIA KABUPATEN ENDE TAHUN 2017 - 2019 - Lukas Nusa Wedo Lewa; Gabriel Tanusi (ANALISIS, 2021)
The purpose of this study is to examine and analyze the financial performance of cooperatives in the Ende regency of Indonesia from 2017 to 2019. This study is descriptive in nature. Documentation and interviews were utilized to obtain data. Cash flow ratio analysis was used in the data analysis, which included the following cash flow ratios: operating cash flow ratio, fund flow coverage ratio, cash to interest coverage ratio, cash coverage ratio to current liabilities, capital expenditure ratio, total debt ratio, cash flow coverage ratio, and free net cash flow ratio. The findings of this study show that the financial performance of cooperatives Pegawai Republik Indonesia, Ende Regency in the years 2017 – 2019 was generally poor because of the eight cash flow ratios used, only two of which meet the standards above one, namely cahs to interest coverage ratio and free net cash flow ratio, while the other six are below standard one, namely operating cash flow ratio, fund flow coverage ratio, cash coverage ratio to current liabilities, capital adequacy ratio, capital adequacy Cooperative management has been unable to control the flow of cards and must enhance cash inflows while decreasing cash outflows.